The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.12962/j25481479.v1i2.1966
|View full text |Cite
|
Sign up to set email alerts
|

Technical Analysis Ballast Water Treatment By Using Economizer Utilizing Main Engines Exhaust Heat To Comply With International Ship Ballast Water Management At Mv. Leader Win

Abstract: Abstract based on the International Ballast Water Management regulations (IBWM), waste water ballast itself has the attention of some researchers to reduce the amount of waste species present in the ballast water with a variety of methods, as of biological, physical, mechanical, and chemical. The decision-making tools such as ballast water heater, flow-through system and others where possible these tools can minimize waste species in ballast water at a certain temperature or pressure of the flow according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…To save space in a vessel with a clean water tank size, clean water should not only be provided at the harbor, but clean water is also provided through seawater desalination technology to fresh water. In addition to other desalination technology distillation is Reverse Osmosis technology(RO) [7].…”
Section: Introductionmentioning
confidence: 99%
“…To save space in a vessel with a clean water tank size, clean water should not only be provided at the harbor, but clean water is also provided through seawater desalination technology to fresh water. In addition to other desalination technology distillation is Reverse Osmosis technology(RO) [7].…”
Section: Introductionmentioning
confidence: 99%
“…With the difference in environmental conditions, the charge will be affected by micro-climate elements, especially air humidity [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study will analyze the characteristics of sloshing movement and direction of movement associated with the sloshing motion of the boat [10]. With the sloshing analysis showed that the walls of the tank which parts are experiencing the greatest potential damage when the pitching and heaving [5,6].…”
mentioning
confidence: 99%